Dampak Iklan Terhadap Penjualan Perusahaan PT. Sido Muncul Tbk (2021—2024) - Husni Mubarok; Diana Oktavia Lestari; Tiara Zettira Rahma; Adinda Kusuma Wardani; Rofiah Fauziah; Marsya Anisa Putri Pohan (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
The purpose of this research is to examine the influence of advertising impact on sales at PT Sido Muncul Tbk 2021-2024. In a competitive business environment, advertising plays an important role in introducing products and creating brand image. As for this research using quantitative approach. The results of this study indicate that advertising has a positive and significant impact on increasing sales. The findings confirm how important an effective advertising strategy is in supporting the company's business growth.